Contribution to Knowledge of the Genus Apsectus (Coleoptera, Dermestidae, Trinodinae) from Mexico and Neotropical Region - Hava, J. (Вестник зоологии, 2012)
Apsectus kaliki sp. n. from Guyana is described, illustrated and compared with all the known Neotropical species of the genus Apsectus LeConte, 1854. Lectotypes are designated for Apsectus centralis Sharp, 1902 and Apsectus hystrix Sharp, 1902.